2019
DOI: 10.3389/fnana.2019.00084
|View full text |Cite
|
Sign up to set email alerts
|

Transduction of Craniofacial Motoneurons Following Intramuscular Injections of Canine Adenovirus Type-2 (CAV-2) in Rhesus Macaques

Abstract: Reliable viral vector-mediated transgene expression in primate motoneurons would improve our ability to anatomically and physiologically interrogate motor systems. We therefore investigated the efficacy of replication defective, early region 1-deleted canine adenovirus type-2 (CAV-2) vectors for mediating transgene expression of fluorescent proteins into brainstem motoneurons following craniofacial intramuscular injections in four rhesus monkeys (Macaca mulatta). Vector injections were placed into surgically i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…Furthermore, CAV has been successfully used in a broad diversity of cortical and subcortical projection pathways (Table 1). Even though rodents were used as the animal models in most of CAV applications in Table 1, recently, CAV was also successfully used in non-human primates ( Table 1; Mestre-Francés et al, 2018;Bohlen et al, 2019;Dopeso-Reyes et al, 2019). These studies validate the applicability of CAV as a gene delivery tool in nonhuman primates, facilitating the investigation of neural circuits in a more human-relevant model.…”
Section: Beneficial Properties Of Cav For Circuit Analysismentioning
confidence: 81%
See 3 more Smart Citations
“…Furthermore, CAV has been successfully used in a broad diversity of cortical and subcortical projection pathways (Table 1). Even though rodents were used as the animal models in most of CAV applications in Table 1, recently, CAV was also successfully used in non-human primates ( Table 1; Mestre-Francés et al, 2018;Bohlen et al, 2019;Dopeso-Reyes et al, 2019). These studies validate the applicability of CAV as a gene delivery tool in nonhuman primates, facilitating the investigation of neural circuits in a more human-relevant model.…”
Section: Beneficial Properties Of Cav For Circuit Analysismentioning
confidence: 81%
“…Moreover, an ideal gene delivery vector should also avoid host immune responses and cytotoxicity. Indeed, CAV viruses are not human pathogens and do not induce significant cellular infiltration in rat brains (Soudais et al, 2004), nor in rhesus monkeys, unless abnormally high titers are used (Bohlen et al, 2019). Even a pre-existing immunity against human adenoviruses does not significantly affect CAV transduction (Klonjkowski et al, 1997;Kremer et al, 2000;Ibanes and Kremer, 2013).…”
Section: Beneficial Properties Of Cav For Circuit Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, it is efficiently retrogradely transported along axons (Salinas et al, 2009 ), while a helper-dependent CAV-2 has been shown to drive transgene expression in the rodent CNS for over a year (Soudais et al, 2004 ). CAV-2 injection into craniofacial muscles of rhesus monkeys caused robust motor neuron transduction (Bohlen et al, 2019 ), while intramuscular administration in rats results in superior motor neuron uptake and transport compared to AdV serotype 5 (Soudais et al, 2001 ), which together highlight the potential of CAV-2 for motor neuron targeting via skeletal muscle.…”
Section: Gene Therapy Virusesmentioning
confidence: 99%